Acoustic Correlates of Speech when Under Stress: Research, Methods and Future Directions - Kirchhübel, Christin; Howard, David M.; Stedmon, Alex W. (International Journal of Speech, Language and the Law, 2011)
The aim of this paper is to summarise the acoustical correlates of stress in speech by reviewing relevant empirical studies. Research into speech under stress faces several challenges including the difficulty in defining the concept of stress, limitations in collecting stressed speech experimentally and the problem of quantifying the type and level of stress induced, resulting in very limited comparability between various studies. In summarizing the previous work and evidence, these conceptual and methodological differences are addressed.Changes in respiration and muscle tension have repeatedly been evidenced to be physiological correlates of stress. Based on this, it may be expected that acoustic parameters such as fundamental frequency, intensity and speaking/articulation rate are affected by stress. In general, empirical findings support these predictions but inter-speaker variability must not be overlooked. It is argued that there is a need to move beyond these three parameters, taking into account for example, vowel formants and aspects of voice quality. It is also suggested that future research should aim to control the data gathering process in ways that are appropriate to allow for comparability of results between studies.